Analisis Ekualisasi Pajak Pertambahan Nilai Sebagai Instrumen Evaluasi Kepatuhan WP - Chorry Ruth Lamtiur; Fitria Intani; Ni Putu Desy Damayanthi; Iffatul Khoriah (Universitas Muhammadiyah Metro, 2026)
This study aims to examine tax planning and Value Added Tax (VAT) compliance through a reconciliation approach between financial statements (Income Statement) and tax reports (VAT Periodic Tax Returns). The research employs a quantitative descriptive method by analyzing financial statements and VAT reports for the fiscal year 2024. The findings reveal discrepancies in reported revenues between the two data sources, primarily caused by differences in accounting and tax treatments, including account classification, non-commercial transactions, re-exports, sales returns, and administrative adjustments. After the reconciliation process, the reported values become consistent, indicating that VAT reporting has been conducted comprehensively in accordance with applicable regulations. Furthermore, the study highlights that reconciliation serves as an effective internal control mechanism and a tool for identifying potential tax risks. The results emphasize the importance of integrating tax planning and tax compliance strategies to enhance reporting quality, particularly in response to the evolving VAT policies in 2025